2009
DOI: 10.1166/jnn.2009.j017
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Brewster Angle Microscopy for Photochemical and Photothermal Studies on Thin-Films and Monolayers

Abstract: Transient events in thin films and interfaces have been studied using the technique of time resolved pump-probe nanosecond Brewster angle microscopy. For p-polarized light there is a minimum reflectivity at the Brewster angle. When the interface is viewed with light that is both incident and reflected at the Brewster angle the resulting image is dark. Subsequent small changes is refractive index will then cause an increase in the reflectivity in affected regions providing high contrast images of an altered int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…27 Briefly, the reflectivity and absorption changes of the monolayer can be derived from Fresnel's equations. 24,26,28 The relation between angular shifts and absorption is linear for initially transparent monolayers. Our simulations and calculations have shown that it is possible to independently determine the changes of the real and imaginary part of the complex refractive indexñ…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Briefly, the reflectivity and absorption changes of the monolayer can be derived from Fresnel's equations. 24,26,28 The relation between angular shifts and absorption is linear for initially transparent monolayers. Our simulations and calculations have shown that it is possible to independently determine the changes of the real and imaginary part of the complex refractive indexñ…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Previously we have shown that BAM is a useful tool for studying photodynamics in SP thin films and monolayers. 24,25 Brewster angle reflectometry (BAR), that is reflectometry in the vicinity of Brewster's angle, was used to study transient kinetics of SP monolayers on functionalised fused silica 26 and self-assembled monolayers at the air-water interface. 27 One drawback of the methods applied was the lack of spectral resolution in the kinetic studies due to the limitation of available probe wavelengths from the probe lasers used.…”
Section: Introductionmentioning
confidence: 99%
“…Optical microscopy and spectroscopy techniques are easily applicable, but (stabilized) membranes are also suitable for scanning probe microscopy. Impedance measurements such as quartz crystal microbalance and surface plasmon resonance [55,56] as well as total internal reflection fluorescence to observe single molecules [57,58] as alternative methods for ultra‐fast measurements of proteins in solid supported membranes are also underway [59]. Consequently, the micro and nanostructure of supported membranes with‐ or without integral proteins can be characterized with high spatiotemporal precision, such, for instance, is provided by transmission electron microscopy (TEM) imaging of outer membrane protein structures (e.g., S‐layer protein assemblies) [60,61].…”
Section: Evolving Fields To Be “Under the Umbrella” Of Synthetic Biologymentioning
confidence: 99%
“…where the imaginary part is an extinction coefficient, k, which is proportional to the absorption coefficient a. 35c k = al/4p (7) Thus the two parameters that change upon photo-excitation are the real and the imaginary parts of the refractive index of the film. They will both contribute to the change of the reflectance:…”
Section: Theoretical Considerations For Data Handlingmentioning
confidence: 99%
“…An additional advantage is that the BAM technique can also be used in pump-probe imaging mode with mm space resolution. [7][8][9] In the current work, the BAM method combined with pulsed laser excitation has been used to elucidate relevant photochemical parameters of the photocolouration, photobleaching and thermal fading reactions for the system of SP immobilised onto fused silica using silane coupling reagents. Thus this method opens an alternative way in which to study the photochemistry of monolayers in which the absorbance changes are otherwise extremely difficult to measure.…”
Section: A Introductionmentioning
confidence: 99%